2013
DOI: 10.2527/jas.2012-5548
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal nutritional manipulation by in ovo enrichment influences bone structure, composition, and mechanical properties

Abstract: The objective of this study was to examine the effect of embryonic nutritional enrichment on the development and properties of broiler leg bones (tibia and femur) from the prenatal period until maturity. To accomplish the objective, 300 eggs were divided into 2 groups: a noninjected group (control) and a group injected in ovo with a solution containing minerals, vitamins, and carbohydrates (enriched). Tibia and femur from both legs were harvested from chicks on embryonic days 19 (E19) and 21 (E21) and d 3, 7, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
30
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 62 publications
6
30
0
1
Order By: Relevance
“…In concurrence to our observation on post‐hatch growth performance, most of the earlier works have reported in ovo administration of zinc did not improve growth performances of post‐hatch chicks (Tako et al., ; Goel et al., ; Yair et al., ; Oliveira et al., ). On the contrary, Joshua et al.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In concurrence to our observation on post‐hatch growth performance, most of the earlier works have reported in ovo administration of zinc did not improve growth performances of post‐hatch chicks (Tako et al., ; Goel et al., ; Yair et al., ; Oliveira et al., ). On the contrary, Joshua et al.…”
Section: Discussionsupporting
confidence: 92%
“…Yair et al. () observed in ovo administration of 0.6 mg zinc/egg in the form of bioplex zinc along with other minerals and vitamins reduced the hatchability to 86.4% compared to control (90.9%). However, the length, weight and relative weight of tibia and femur were higher on day 14 which showed improved mechanical properties (stiffness, maximal load) compared to control.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the mammalian embryo, chick embryos must rely upon egg nutrients independently, so sufficient nutrients in the egg will enable a good starting for the hatching chicks. However, studies have indicated that nutrient reserves in the egg are insufficient to fully support embryonic development . In ovo feeding (IOF) is a method of supplementing exogenous nutrients into the avian embryo to enhance egg nutrition and posthatch growth.…”
Section: Introductionmentioning
confidence: 99%
“…The in-ovo method was first used by Sharma & Burmester (1982) for the vaccination of turkey hatching eggs against Marek's disease. Recently, the in-ovo method has been investigated by researchers for administering ascorbic acid (Elibol et al, 2001;Ipek et al, 2004;Sgavioli et al, 2015), carbohydrates (Zhai et al, 2011;Salmanzadeh, 2012;Ipek et al, 2004;Tako et al, 2004), amino acids (Bhanja et al, 2014;Ohta et al, 1999;Kermanshahi et al, 2015), vitamins (Bello et al, 2013;Salary et al, 2014), minerals (Yair et al, 2013;Oliveira et al, 2015), pollen (Coskun et al, 2014), hormones (Moore et al, 1994;Kocamis et al, 1999), and royal jelly (Moghaddam et al, 2014).…”
Section: Introductionmentioning
confidence: 99%